Салтово-маяцкие памятники Центральной и Северной части Керченского полуострова (материалы к археологической карте) - Пономарёв, Л.Ю. (Хазарский альманах, 2020)
The article provides a brief overview of the Saltovo-Mayack settlements and burial grounds located in the central and northern part of the Kerch Peninsula. Unfortunately, only a few of the settlements were excavated. The work was limited to visual observations and the collection of fi nds on the surface.